Physical Infrastructure Projects Under Threat: The Impact of Violence and Extortion on South African Construction Sites - Dladla, Bongani; Aigbavboa, Clinton; Ebekozien, Andrew; Akinrdewo, Opeoluwa (Journal of Posthumanism, 2025)
Purpose – Studies have shown that organised crime groups are fast increasing on construction sites, especially in many developing countries, with agitation that has culminated in violence, disruptions, and criminal extortion. This may threaten physical infrastructure project delivery in low-income countries. There is a paucity of extant literature concerning the impact of violence and extortion on South African construction sites. Thus, this research investigates the perceived impact and suggests collaborative efforts to mitigate the impact of violence and extortion on South African construction sites and, by extension, achieve physical infrastructure project delivery. Design/methodology/approach – The research adopted a qualitative research design. The investigators collected primary data via semi-structured interviews with participants. The interviewees were knowledgeable about violence and extortion on South African construction sites and achieved saturation. This research also employed a thematic technique to analyse the data manually. Findings – Findings reveal that the physical infrastructure projects are worse hit by the consequences of violence and extortion on South African construction sites and identified murder, worker intimidation, cost overruns, project disruption, increased security expenses, abandonment, job cut, economic downturns, broader economic repercussions, and threats of lives as impact of violence and extortion on South African construction sites and their aftermath to physical infrastructure projects. Originality/value – Besides all-inclusive mechanisms to mitigate the impact of violence and extortion on South African construction sites, this study emphasises collaborative efforts to mitigate the social threat to physical infrastructure development. This includes collaborations with law enforcement, community-based security models, and integration with private security.